2013
DOI: 10.1177/1071100713502641
|View full text |Cite
|
Sign up to set email alerts
|

Flexor Digitorum Brevis Transfer for Floating Toe Prevention after Weil Osteotomy

Abstract: Continued research in this subject will help to refine methods of prevention and correction of the floating toe deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…First, a low TGS is associated with floating toe. Previous studies6, 16 ) reported that the windlass mechanism may be responsible for post-osteotomy floating toe. TGS is exerted mainly by the plantar intrinsic and extrinsic muscles17 ) , which play a role in the windlass mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…First, a low TGS is associated with floating toe. Previous studies6, 16 ) reported that the windlass mechanism may be responsible for post-osteotomy floating toe. TGS is exerted mainly by the plantar intrinsic and extrinsic muscles17 ) , which play a role in the windlass mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…Shortening the metatarsal and positioning the center of rotation of the metatarsal head slightly dorsal to the intrinsic musculature, it allows for a more anatomical vector with increased lever arm for the musculature to pull the proximal phalanx plantarly, correcting the MTPJ dorsiflexion deformity [43]. Fair to good functional results were reported, but a high percentage of complications have been associated with these procedures, particularly floating toes and MTPJ stiffness [18,19,44,45]. Although biomechanically sound, the fact that the surgery is most commonly and traditionally performed open, and consists of an intraarticular osteotomy, it is inherently associated with increased scar tissue formation, dorsiflexion contracture (floating toes) and MTPJ stiffness [15].…”
Section: Discussionmentioning
confidence: 99%
“…The Weil osteotomy is perhaps the standard DMSO technique and consists of an intra-articular oblique osteotomy aligned parallel to the floor [17]. The reported complications of DMSO include recurrence of the sagittal plane component of the deformity, with floating toes presenting in up to 68% of the cases [18,19], as well as frequent and considerable MTPJ stiffness. The intraarticular or intracapsular characteristic of these osteotomies, associated with the need for extensive dorsal soft tissue dissection, is deemed to be partially responsible for the prevalence of these complications [19].…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of the FDB to the proximal interphalangeal joint has been found effective in the prevention of floating toes after Weil osteotomy [13] and in toe ulcers of claw-or hammer-toes in diabetic patients [14]. FDB transfer to the interosseous and lumbrical muscles has been effectively used in treating dynamic claw toe deformity [15].…”
Section: Discussionmentioning
confidence: 99%